Finnish Teachers’ Professional Autonomy from a Relationality Perspective - Ince, Akif (My University, 2024)
This thesis explores Finnish teachers’ autonomy from a relational justice perspective, highlighting the interconnectedness of teaching practices within a network of social relationships and responsibilities. Moving beyond the traditional dichotomy of autonomy versus constraints, it adopts the concept of relational autonomy to investigate the intricate interplay between autonomy and collaboration in Finnish school contexts. The theoretical framing emphasizes solidarity within the school culture and shifts the focus from individual decision-making to the teachers’ relationships with other teachers, parents, and principals. The study poses two questions: the dimensions of teachers’ autonomy and solidarity in school culture, and whether these can be conceptualized as relational autonomy. The research design is based on generic qualitative research involving semi-structured interviews with nine Finnish teachers – four of whom are candidate teachers. For the analysis of data, the study employs reflexive thematic analysis to delve into the complexities of teacher autonomy and solidarity in school culture. Findings reveal that autonomy, intertwined with collaboration, evolves with professional socialization and the cultivation of a communal professional ethos. This ethos is facilitated by dynamic negotiations and support among teachers, principals, and parents within a well-structured social and institutional context. In this context, the curriculum plays a pivotal role in shaping teachers’ responsibilities and infusing a sense of duty as well as aligning their teaching practices with other teachers. Additionally, the role of testing extends beyond student assessment to impact on other teaching domains (planning and instruction) and overall teacher autonomy. The study concludes that teacher autonomy is inherently relational, and emerges from solidarity, founded on trust, mutual support, and collective goals.
Keywords: Relational autonomy, relational justice, solidarity, collaboration, Finnish teachers